PENGARUH FINANCIAL LITERACY DAN LIFESTYLE TERHADAP FINANCIAL MANAGEMENT BEHAVIOUR PADA PNS DENGAN SELF CONTROL SEBAGAI VARIABEL INTERVENING DALAM PERSPEKTIF EKONOMI ISLAM (Studi Pada Pegawai Negeri Sipil Di Bandar Lampung) - Ice Marwiyah; Fatih Fuadi; Mia Selvina (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the influence of Financial Literacy and Lifestyle on Financial Management Behavior in Bandar Lampung City, with Self-Control as an intervening variable. The method used is a questionnaire with a sample of 100 respondents selected randomly from several civil servants in Bandar Lampung. This research is quantitative in nature. The sampling technique used is probability sampling. This study uses data analysis techniques applied is PLS (Partial Least Squares) by utilizing SmartPLS software. The research findings show that Financial Literacy does not affect Financial Management Behavior, while Lifestyle also does not affect Financial Management Behavior. On the other hand, Self-Control has a positive and significant effect on Financial Management Behavior. In addition, Financial Literacy has a negative and significant effect on Self-Control and Lifestyle has a positive and significant effect on Self-Control. On the other hand, Self-Control is able to mediate the influence of Financial Literacy on Financial Management Behavior but has a negative effect. Similarly, Self-Control is able to mediate the influence of Lifestyle on Financial Management Behavior. This research was conducted from the perspective of Islamic economics and focuses on civil servants in Bandar Lampung City.